Effects of social framing for environmental persuasion in Japan and the United States: a brief report - Foster, Melissa; Cho, Hyunyi (Frontiers in Communication, 2026)
Highlighting social outcomes of behaviors may be useful for pro-environmental persuasion, but the focus of the social outcome may need to be different across cultures. For example, social outcomes could focus on benefits to the individual via approval of other people in one’s ingroup or benefits to the collective due to improvements to the environment. For two countries (Japan and America) and two environmental topics (plastic straws use and hoarding), we examined two dimensions of social framing: emphasizing positive outcomes for either shared benefits or one’s social image. The 1,398 participants, recruited from Japan and the United States, viewed a social media-style message and shared their reactions to it and interest in pro-environmental behaviors. The framing manipulation did not have direct effects on policy support or behavioral intentions for either country. However, social image framing led to more psychological reactance for Americans but not for Japanese. Higher reactance predicted lower intended outcomes for participants who were high on self-orientation, but this effect was only observed for Americans regarding plastic straw use. Practical implications of these results include taking care in message design to avoid eliciting psychological reactance, especially for topics that are complex, important for the global future, and require culturally aware communication practices. Theoretical implications include encouraging further clarification between collectivist and individualistic messages since collectivist (social) messages can appeal to personal or collective benefits and suggested boundary effects for when reactance can negatively impact outcomes.